Kebijakan Pemerintah terhadap Pendidikan Inklusif - Santi Mulyah; Qolbi Khoiri (Departement of Mathematics Education, 2023)
Inclusive education is the education given to students who have the disorder, has the potential intelligence and special talents. Also children are not able to learn for one thing: disability, autism, mental retardation, homeless children, the other had the talent and potential. Inclusive education is a system of educational services for children with special needs in the regular school education and this should be done as early as possible. This is in accordance with the policy internationally and nationally as stipulated in Law No. 20 of 2003 on article 32 and Permendiknas number 70 of 2009, by providing opportunities and opportunities for children with special needs to acquire education in schools regular ranging from elementary school, School junior High and High School / Vocational. The success of inclusive education will depend on the cooperation of the government, teachers and parents together.